Analisis Komparatif Implementasi Pendidikan STEM di Berbagai Negara di Asia Tenggara: Pendekatan Pedagogis, Temuan Utama, dan Tantangan - Bahri, Husnaini; Syahrul, Muhammad (PT. Ininnawa Paramacitra Edukasi, 2025)
Science, Technology, Engineering, and Mathematics (STEM) education has become a strategic approach to developing 21st-century skills and enhancing global competitiveness. The implementation of STEM across Southeast Asia shows significant variation. This study aims to comparatively analyze the pedagogical approaches, key findings, and implementation challenges of STEM education in eight ASEAN countries using a systematic literature review approach. Data were collected from relevant scholarly publications using the Google Scholar search engine and analyzed based on three categories: pedagogical approach, implementation outcomes, and challenges. The findings reveal that countries such as Singapore and Vietnam have successfully built progressive STEM education ecosystems through policy support, continuous teacher training, and adequate infrastructure. Meanwhile, developing countries such as Indonesia, Malaysia, Thailand, and the Philippines face challenges such as unintegrated curricula, limited resources, and low teacher readiness. This study concludes that the success of STEM education heavily depends on the synergy between national policies, teacher preparedness, and supporting facilities. The results are expected to serve as a foundation for designing adaptive and contextual STEM implementation strategies across Southeast Asia.